IMPLEMENTASI MIND MAPPING PEMBELAJARAN FIQIH BERBASIS KURIKULUM TIMUR TENGAH - Fikri Tajdidi, Ghifarul; Ida Rindaningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of the mind mapping approach in learning fiqh based on the Middle East Curriculum at MBS A.R. Fachruddin Yogyakarta. Qualitative method with a phenomenological approach that aims to collect data about the phenomenon under study without generalisation. The results showed that mind mapping helps students understand complex fiqh concepts more systematically, improves memory, and encourages active involvement and critical thinking of students during the learning process. Implementation was carried out on 30 junior high school students in class IX and was carried out in three stages: planning, implementation, and evaluation, with study material on the Zakat Fitrah chapter in the book of Zaadul Mustaqni. There were several obstacles encountered during the implementation of the mind mapping approach, such as the teacher's adaptation to the new method, the narrow time in teaching preparation, the preparation of material that is easy to visualise and the students' different thinking abilities. This research confirms that the mind mapping approach can be a bridge between the traditional talaqqi method and the needs of more modern and participatory learning.